2022
DOI: 10.3389/fcvm.2022.810334
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue and Postoperative Atrial Fibrillation

Abstract: BackgroundAtrial fibrillation (AF) often occurs after cardiac surgery and is associated with increased risk of stroke and mortality. Prior studies support the important role of inflammation in the pathogenesis of postoperative atrial fibrillation (POAF). It is known that an increased volume and a pro-inflammatory phenotype of epicardial adipose tissue (EAT) are both associated with AF onset in non surgical context. In the present study, we aim to evaluate whether also POAF occurrence may be triggered by an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(42 reference statements)
2
8
0
Order By: Relevance
“…In pathological contexts, EAT switches from an anti-inflammatory phenotype to a pro-inflammatory phenotype, mediated in part by the release of fatty acids and pro-inflammatory adipokines, including interleukin-1b, interleukin-6, activin-A, and tumor necrosis factor-alpha ( 33 ). These pro-inflammatory cytokines have been reported to be associated with POAF after cardiac surgery ( 15 , 16 ). To a certain extent, the EAT volume and radiodensity reflect its pathological status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pathological contexts, EAT switches from an anti-inflammatory phenotype to a pro-inflammatory phenotype, mediated in part by the release of fatty acids and pro-inflammatory adipokines, including interleukin-1b, interleukin-6, activin-A, and tumor necrosis factor-alpha ( 33 ). These pro-inflammatory cytokines have been reported to be associated with POAF after cardiac surgery ( 15 , 16 ). To a certain extent, the EAT volume and radiodensity reflect its pathological status.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial adipose tissue (EAT) is a special visceral adipose tissue located between the myocardium and the visceral pericardium ( 14 ). It produces numerous pro-inflammatory cytokines which can promote the development of POAF ( 15 , 16 ). Quantitative analysis of EAT can be performed by cardiac computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there are no fascial boundaries between the atrium and the ventricles, thus, multiple adipose cytokines secreted by EAT around the left ventricle can reach the atrium and affect atrial fibrosis [7]. A variety of inflammatory mediators secreted by EAT are also closely related to the occurrence of AF [8]. In addition, EAT is rich in autonomic ganglion plexus, and the excitation of sympathetic and parasympathetic nerves can increase intracellular calcium concentration and shorten action potential duration, thus promoting the occurrence and development of AF [9].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β stimulates activin A expression ( Arai et al, 2011 ) that has been reported to be produced by epicardial adipose tissue (EAT) of patients evolving POAF after cardiac surgery ( de Kretser et al, 2012 ; Wang et al, 2019 ). We recently reported an increased inflammatory status of EAT also in POAF ( Petraglia et al, 2022 ). However, further evidence is required to confirm all these hypothetic mechanisms in order to clarify the role of EAT in cardiovascular disease and AF.…”
Section: Introductionmentioning
confidence: 93%